The Personal Web A Research Agenda - Chignell, Mark.; Cordy, James R.; Kealey, Ryan.; Ng, Joanna; Yesha, Yelena; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book grew out of the First Symposium on the Personal Web, co-located with CASCON 2010 in Markham, Ontario, Canada. The purpose of the symposium was to bring together prominent researchers and practitioners from a diverse range of research areas relevant to the advancement of science and practice relating to the Personal Web. Research on the Personal Web is an outgrowth of the Smart Internet initiative, which seeks to extend and transform the web to be centred on the user, with the web as a calm platform ubiquitously providing cognitive support to its user and his or her tasks. As with the preceding SITCON workshop (held at CASCON 2009), this symposium involved a multi-disciplinary effort that brought together researchers and practitioners in data integration; web services modelling and architecture; human-computer interaction; predictive analytics; cloud infrastructure; semantics and ontology; and industrial application domains such as health care and finance. The discussions during the symposium dealt with different aspects of the architecture and functionality needed to make the Personal Web a reality. After the symposium the authors reworked their presentations into draft chapters that were submitted for peer evaluation and review. Every chapter went through two rounds of reviewing by at least two independent expert reviewers, and accepted chapters were then revised and are presented in this book.
The Personal Web -- PWWM: A Personal Web Workflow Methodology -- Service Subscription and Consumption for Personal Web Applications -- A Framework for Composing Personalized Web Resources -- A Privacy Framework for the Personal Web -- Intelligence for the Personal Web -- Communities, Artifacts, Interaction and Contribution on the Web -- The SmarterContext Ontology and Its Application to the Smart Internet: A Smarter Commerce Case Study -- Simplifying the Task of Group Gift Giving.
Keywords: Computer science; Software engineering; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Software Engineering; Information Storage and Retrieval; User Interfaces and Human Computer Interaction